The Accountability Of The National Land Agency For The Issuance Of Double Land Certificates - Sriwahyuni, Dewi (International Significance of Notary, 2023)
Abstract : A certificate is a valid proof of ownership what if there are multiple certificates, who is responsible for this is what the author raises with the formulation of the problem, including, 1) Legal Consequences of Multiple Land Certificates issued by the National Land Agency, 2) Forms of Accountability of the National Land Agency For Double Land Certificates that have been issued, 3) Settlement by the National Land Agency for Double Land Certificates that have been issued. The method used in this study is to use normative juridical research methods. Legal Approach.The results of the research on the Legal Consequences of Multiple Land Certificates issued by the National Land Agency are Causing legal uncertainty, public distrust of government agencies or the Ministry of Agrarian Affairs, Losses for both parties to the dispute, especially for those who are declared defeated in court, Cancellation or revocation of certificates based on Decisions State Administrative Court which has permanent legal force.Forms of Accountability of the National Land Agency for Multiple Land Certificates What has been issued is that the National Land Agency is directly responsible for all land issues related to the granting of rights and the issuance of multiple land certificates for the inaccuracy of the BPN in issuing the certificates,Among others 1) Principle of Responsibility Based on Elements of Error 2) Responsibility in Civil Law 3) Responsibility in Criminal Law 4) Responsibility in Administrative LawSettlement by the National Land Agency for Double Issued Land Certificates is a direct settlement by the party in consultation with the BPN mediator, this is in accordance with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases other than that Through arbitration and alternative dispute resolution.Keywords: Accountability, BPN, Double Certificate,